A national implementation approach for exercise as usual care in pediatric and adolescent oncology: Network ActiveOncoKids - Götte, Miriam; Söntgerath, Regine; Gauß, Gabriele; Wiskemann, Joachim; Buždon, Mirko; Kesting, Sabine (Pediatric exercise science, 2022)
The diagnosis of cancer as well as accompanying acute and late effects of treatment are influencing physical activity behavior of patients with childhood cancer and survivors. Research has shown that a pediatric cancer diagnosis is associated with impairments of physical performance, and function, as well as reduced physical, and psychosocial, health conditions. From an ethical perspective, lack of knowledge of health care providers, lack of physical activity promotion, and environmental, and structural barriers to physical activity restrict children’s right to move and actively engage in physical activities. Network ActiveOncoKids is a German-wide initiative with the main goal of enabling children, adolescents, and young adults with exercise opportunities during and after cancer treatment. Since the network’s foundation in 2012, Network ActiveOncoKids focuses on: (1) physical activity support for patients and families, (2) policy change to establish structures and guidelines, and (3) generating evidence through scientific projects. The purpose of this paper is to present an overview of Network ActiveOncoKids structure, aims, and projects. This topical review will highlight the network’s structural development, research work, and implementation progress of exercise programs for patients with pediatric cancer and survivors, link international collaborations, and discuss future directions.
Gesehen am 24.01.2023